3 1 2

3 2 -1

1 1 1
in Calculus Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Work out the determinant: 3(2+1)-1(3+1)+2(3-2)=9-4+2=7.

Take each column and make it into a row:

3  3 1

1  2 1

2 -1 1

Replace each element with its subdeterminant:

(2×1-1×-1)=3  (1×1-1×2)=-1 (1×-1-2×2)=-5

(3×1-(-1)×1)=4 (3×1-1×2)=1 (3×-1-3×2)=-9

(3×1-1×2)=1 (3×1-1×1)=2 (3×2-3×1)=3

Change the sign of every other element and divide by the determinant:

( 3  1 -5)

(-4  1  9) ÷ 7

(1 -2  3)

Check the result by applying to the original matrix:

( 3  1 -5)(3  1  2)

(-4  1  9)(3  2 -1) ÷ 7

(1 -2  3)(1  1  1)=

(1 0 0)

(0 1 0)

(0 0 1)

The result is the identity matrix, so the inverse is correct.

 

by Top Rated User (663k points)

Related questions

1 answer
1 answer
asked Jan 3, 2012 in Algebra 2 Answers by anonymous | 510 views
1 answer
asked Jul 3, 2013 in Word Problem Answers by anonymous | 81 views
1 answer
0 answers
0 answers
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
83,225 questions
88,062 answers
1,980 comments
4,947 users